The Effect of PPARα, PPARδ, PPARγ, and PPARpan Agonists on Body Weight, Body Mass, and Serum Lipid Profiles in Diet-Induced Obese AKR/J Mice. (6th June 2007) - Harrington, W. Wallace; Britt, Christy S.; Wilson, Joan G.; Milliken, Naphtali O.; Binz, Jane G.; Lobe, David C.; Oliver, William R.; Lewis, Michael C.; Ignar, Diane M.
Abstract : Activation of peroxisome proliferator-activated receptor (PPAR)α, δ, andγ subtypes increases expression of genes involved in fatty acid transport and oxidation and alters adiposity in animal models of obesity and type-2 diabetes. PPARpan agonists which activate all three receptor subtypes have antidiabetic activity in animal models without the weight gain associated with selective PPARγ agonists. Herein we report the effects of selective PPAR agonists (GW9578, a PPARα agonist, GW0742, a PPARδ agonist, GW7845, a PPARγ agonist), combination of PPARα andδ agonists, and PPARpan (PPARα / γ / δ ) activators (GW4148 or GW9135) on body weight (BW), body composition, food consumption, fatty acid oxidation, and serum chemistry of diet-induced obese AKR/J mice. PPARα or PPARδ agonist treatment induced a slight decrease in fat mass (FM) while a PPARγ agonist increased BW and FM commensurate with increased food consumption. The reduction in BW and food intake after cotreatment with PPARα andδ agonists appeared to be synergistic. GW4148, a PPARpan agonist, induced a significant and sustained reduction in BW and FM similar to an efficacious dose of rimonabant, an antiobesity compound. GW9135, a PPARpan agonist with weak activity at PPARδ, induced weight loss initially followed by rebound weight gain reaching vehicle control levels by the end of the experiment. We conclude that PPARα and PPARδ activations are critical to effective weight loss induction. These results suggest that the PPARpan compounds may be expected to maintain the beneficial insulin sensitization effects of a PPARγ agonist while either maintaining weight or producing weight loss.